Karakteristik Fisikokimia Minuman Serbuk Instan Dengan Variasi Bonggol Nanas (Ananas comosus Merr) dan Maltodekstrin - Amalya Nurul Khairi; Nadya Furayda (Pasundan Food Technology Journal (PFTJ), 2023)
Powder drink is a more practical form of functional drink development from pineapple humps. Pineapple weevil is a waste of pineapple production which contains vitamin C and antioxidants. The heating process using high temperatures for a long time can damage the vitamin C and antioxidant content. The addition of maltodextrin as a filler can inhibit heat damage and increase the solubility of powdered drinks. The purpose of this study was to analyze the physicochemical properties of powdered drinks with variations of pineapple weevil and maltodextrin. This study used a one-factor Completely Randomized Design (CRD), namely the comparison of pineapple humps and maltodextrin. Parameters observed were physical characteristics (solubility, yield) and chemical (pH, moisture content, ash content, vitamin C, and antioxidants). The results showed that the addition of maltodextrin to powdered drinks increased the yield value of 3.72%, solubility of 25.86%, and pH of 3.1%, but decreased the value of the water content of 0.47%, ash content of 0.22%, vitamin C content. 42.9%, and 8.8% antioxidant activity.